Implementation of PT X's Corporate Social Responsibility (CSR) Program in Suku Baduy, Lebak District, Banten Province - Hidayat, Dedi; Hermawan, Asep (International Journal Labs, 2023)
This study aims to determine the relationship between the characteristics of the Baduy Tribe and the “Saba Budaya Baduy” on the implementation of the CSR Program in the Baduy Tribe and to analyze the implementation of the PT X CSR Program in the Baduy Tribe which consists of forms, benefits and challenges. This study used a qualitative descriptive approach with informants consisting of the Baduy Tribe (Inside and Outer), Lebak District Tourism Office, and Buffer Village in the Baduy tribal area. The Baduy tribe has limitations, including the economic, health, infrastructure, and environmental aspects so the company's CSR contribution becomes very important. The Baduy tribe has distinctive characteristics that adhere to customary rules (Pikukuh Karuhun). The results of the study show that the characteristics of the Baduy tribe are closely related to the implementation of CSR programs by companies in the Baduy tribeThe form of CSR implemented by PT X in the Baduy Tribe consists of health service programs and supporting infrastructure for Baduy Tourism or Saba Budaya Baduy. The managerial implication for the company is that it is necessary to conduct a study of the characteristics of the Baduy Tribe and the Social Need Assessment so that the CSR program that will be implemented is to the needs of the Baduy Tribe. Furthermore, the company needs to coordinate with the related government. The policy implication for the government is to provide support and facilitation as well as provide information related to the characteristics of the Baduy tribe to companies that will implement CSR programs in the Baduy tribe.